Cases of apparent enclisis on past participles in Romance varieties - Anna Cardinaletti (Universitat Autònoma de Barcelona, 2015)
This paper deals with cases of apparent enclisis on past participles in North-Western Italian varieties. It is claimed that these cases do not involve clitic pronouns, but weak pronouns in the sense of Cardinaletti and Starke (1999). Both syntactic and morphophonological evidence is discussed. Some varieties display both proclitics and postverbal weak pronouns and use them in different syntactic contexts. Other varieties lack clitic pronouns in their lexicon altogether and only display weak pronouns (alongside strong pronouns), similarly to what happens in e.g. Germanic languages.